(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article discusses the current picture of public perception of sustainable tourism in Gegharkunik Region. The purpose of the work is to study and identify how much the population of Gegharkunik Region is aware of sustainable tourism. In the course of the work, a study was conducted and an electronic sociological survey was conducted to understand the current perception of sustainable tourism. The analytical results of the sociological survey showed that the implementation of the concept of sustainable tourism undoubtedly requires targeted and coordinated steps, from the very beginning giving specific attention to overcoming barriers of insufficient awareness of the population. In the region, the public perception of tourism as a priority sector of the economy, its role and importance, its decent assessment and proper use are now vital. Conversely, incorrect public perception, underestimation and irrational use of resources become a problem. Sustainable tourism is important both for the preservation of the environment and for the socio-economic development of the region and communities. In the region, it should be based on the principles of rational use of natural resources, preservation of cultural values and social justice. Proper public perception in this area can have a significant impact on the development and dissemination of sustainable tourism ideas. Daily human activities lead to environmental degradation in combination with a significant increase in mass tourism․ In this case, the negative impact of the anthropogenic factor on the environment as a result of mass tourism is obvious, which becomes a serious challenge for the environment. Sustainable tourism in this case serves as a methodological platform for all types of tourism.